Three-Stage Amplifier Adopting Dual-Miller with Nulling-Resistor and Dual-Feedforward Techniques - Zhou Qianneng; Li Qi; Li Chen; Lin Jinzhao; Li Hongjuan; Li Yunsong; Pang Yu; Li Guoquan; Cai Xuemei (Institute of Advanced Engineering and Science, 2014)
A high-gain wide-bandwidth three-stage amplifier, which employs dual-miller compensation with nulling-resistor and dual-feedforward compensation (DMCNR-DFC), is designed and analyzed in this paper. By adopting the technique of DMCNR-DFC, the designed three-stage amplifier achieves well performance including gain-bandwidth product (GBW) and slew rate (SR). The improved DMCNR-DFC three-stage amplifier is designed and simulated in 0.5μm BCD process. Simulation results show that DMCNR-DFC three-stage amplifier achieves a dc gain of about 121.1dB and GBW of about 6.1MHz with 52º phase margin using a 5-V power supply voltage.